Pancasila Sebagai Kompas Etika Dalam Menghadapi Konflik Di Tempat Kerja - Aulia Nur Indah Ernani; Adi Setiyawan; Cahya Aninda; Fajar Alfadhil (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study aims to analyze the influence of Pancasila values internalization on individuals’ ability to manage and resolve conflicts in the workplace. The background of this research is based on the high potential for conflict in professional environments due to differences in values and interests among individuals. This associative quantitative study used the SEM-PLS method, involving 100 employees with a minimum of one year of work experience. The results indicate that Pancasila values significantly influence conflict management, with a path coefficient of 0.901 and an R Square value of 0.811. This means that 81.1% of the variance in conflict management ability can be explained by the internalization of Pancasila values. Indicator NP1 made the greatest contribution to the Pancasila values construct, while MK2 was the most dominant in the conflict management construct. Validity and reliability tests show that all indicators in the research model meet the required standards. These findings confirm that Pancasila values can serve as a practical ethical guideline in creating a harmonious, professional, and productive work environment.